2022
DOI: 10.33256/32.3.120129
|View full text |Cite
|
Sign up to set email alerts
|

A stable home: Autocorrelated Kernel Density Estimated home ranges of the critically endangered Elongated tortoise

Abstract: Home range analysis is a standard and fundamental concept in ecology used to describe animal space use over their lifetimes. Connecting home range sizes with animal characteristics, location, and habitat can be used to inform conservation decisions. Reptiles are frequently lacking robust estimates of space use, particularly reptiles in tropical regions. Here we analyse a publicly available dataset, collected by the authors of this study, describing the movements of Critically Endangered Elongated tortoises Ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A similar sampling duration (45-136 days) was required in a study on giant anteaters (Myrmecophaga tridactyla), where the average home range crossing time was approximately 2 days (Giroux et al, 2021). In contrast, a study on elongated tortoises (Indotestudo elongata) estimated a home range crossing time of 17 days on average (although sometimes much longer for particular individuals), and even with 1 year of consistent sampling, researchers were not able to achieve adequate effective sample sizes for several individuals (Montano et al, 2021). Studies on Mongolian gazelles have shown estimated range crossing times of around 5-6 months (Fleming et al, 2014a).…”
Section: Species-level Differences In Home-range Crossing Timementioning
confidence: 99%
See 1 more Smart Citation
“…A similar sampling duration (45-136 days) was required in a study on giant anteaters (Myrmecophaga tridactyla), where the average home range crossing time was approximately 2 days (Giroux et al, 2021). In contrast, a study on elongated tortoises (Indotestudo elongata) estimated a home range crossing time of 17 days on average (although sometimes much longer for particular individuals), and even with 1 year of consistent sampling, researchers were not able to achieve adequate effective sample sizes for several individuals (Montano et al, 2021). Studies on Mongolian gazelles have shown estimated range crossing times of around 5-6 months (Fleming et al, 2014a).…”
Section: Species-level Differences In Home-range Crossing Timementioning
confidence: 99%
“…A thorough evaluation of the AKDE compared against commonly used approaches, such as the MCP, KDE, and Local Convex Hull (LocoH), shows that the AKDE is superior in capturing space use out of sample and is the only estimator capable of producing unbiased estimates with low effective sample sizes . While AKDE is increasingly adopted in studies of animal ranging behavior (Crabb et al, 2022;Desbiez et al, 2020;Lenske & Nocera, 2018;McEvoy et al, 2019;Montano et al, 2021;Naveda-Rodríguez et al, 2022;Poessel et al, 2022), the overwhelming majority of studies still use methods, such as the MCP and KDE (Börger et al, 2020;Fleming & Calabrese, 2017;Hemson et al, 2005;Laver & Kelly, 2010;Powell, 2000). The potential presence of significant, systematic biases from applying these methods to estimate home-range area is concerning, because it can lead to erroneous conservation decision-making (Gaston et al, 2008) or inaccurate meta-analyses that influence public opinion and theoretical frameworks (Noonan et al, 2020).…”
mentioning
confidence: 99%
“…To check for AKDE's assumptions on range residency 47 , we first built up individual variograms using the ggplot2 v.3.35 package 48 and visually decided which ones we considered were stable. Secondly, we explored the effective sample size of all individuals (DOF area resulting from the 'akde' function) and retained for home range calculations only those with a value greater than 10 (following Montano et al 49 ). We also calculated home range using the Minimum Convex Polygon (MCP) 50 (100%, 95%, and 50%) and Kernel Density Estimators (KDE) 51 (95% and 50%) to allow comparisons with previous studies.…”
Section: Data Analyses Data Preparationmentioning
confidence: 99%
“…We generated R package citations with the aid of grateful v.0.0.3 61 . The code we used was based upon that used by 62 that is available at https:// osf. io/ rxu6f/.…”
Section: Home Ranges Analysis and Comparisonsmentioning
confidence: 99%